Menstrual Cycle Hormones Induce Changes in Functional Interactions Between Lymphocytes and Decidual Vascular Endothelial Cells - VAN DEN HEUVEL, MARIANNE J. (2005)
During the secretory phase of the menstrual cycle, a Natural Killer (NK) cell subset expressing CD56(bright), appears in the decidualizing uterus, and remains until onset of menses. If pregnancy occurs, decidual (d)NK cells increase to become the predominant uterine lymphocytes of early pregnancy. To elucidate mechanisms of CD56(bright) cell recruitment to the uterus, an in vitro adhesion assay was used to assess the effect of the menstrual cycle, as well as cycle-associated hormones on adhesive properties of human lymphocytes. Adhesion of human peripheral blood lymphocytes to pregnant mouse lymph nodes and Peyer’s Patches tissue sections was constant throughout the cycle. When uterine tissue was used as the substrate, adhesive CD56(+) cells were found only in decidua basalis. Adhesion increased at the luteinizing hormone surge. Adhesion was mediated through both L-selectin and α(4) integrin-dependent mechanisms. Furthermore, we observed increased adhesive function in CD56+ cells from male donors which had been cultured with estradiol or LH as compared to cell aliquots cultured without additives. Lymphocytes adherent to mouse uterine tissue were predominantly CD56(bright), suggesting that peripheral NK cells may be actively recruited to the uterus in an important, brief endocrine-regulated fashion at the time of ovulation to establish the dNK population of early pregnancy.